From a prohibited game to a lucky business. Businessmen and politicians in the lottery business in Mexico, 1915-1933 (Tzintzun, Revista de Estudios Históricos, 2016)
Debates on the morality of lottery generally intermingle with weak publicfunds. Post-revolutionary governments have had diferent views on gamblingcompanies. In the history of public lottery companies in Mexico, we addressdecision-making processes and conlicts of interest between civil servantsand prominent businesspeople which can be observed both on the level ofthe state and federal governments, as well as between public organizationsseeking to gain control over lotteries. his paper looks into the discursive useof social issues and the promise of pushing the beneits as a way to legitimatethe game in front of the state. hrough a novel source study of the archives ofthe Lottery, an analysis is provided of the very complex set of norms and thoseillegal agreements which strengthened state control by adjusting interests,thus generating a signiicant money low between 1915 and 1933.
Keywords: lottery; gambling; public company; social issues; revolutionary factionalism